Effect of Technology Enhanced Language Learning on Vocabulary Acquisition of EFL Learners - Taj, Imtiaz Hassan; Fatimah, Ali; Sipra, Muhammad Aslam; Ahmad, Waqar (Australian International Academic Centre, Australia, 2017)
The study was conducted to investigate the impact of a model, created with the help of computer and mobile phone, on the EFL vocabulary learning of the students at a public university on a Preparatory Year Program. The study used a quasi-experimental pretest posttest control group design. The participants were 122 students in their first year at a public university. Half of them (N = 61) were male and half were female (N = 61). Six weeks treatment period involved vocabulary learning activities presented through PCs in the language laboratory and receiving multi-glossed vocabulary cards on the mobile phones through a social networking mobile phone application WhatsApp. Findings suggested that performance of treatment group was significantly better than that of control group on achievement posttest. The impact of treatment was found gender neutral as male and female participants benefitted from it alike.